In vivo antidiabetic and acute toxicity of spray-dried Vernonia amygdalina water extract - Yeap, Swee Keong; Liang, Woon San; Beh, Boon Kee; Ho, Wan Yong; Noaman, Yousr Abdulhadi; Mohammed Alitheen, Noorjahan Banu (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
The spray-dried Vernonia amygdalina water extract was evaluated for antidiabetic effect using normoglycaemic, glucose induced hyperglycaemic and streptozotocin induced diabetic mice. This effect was compared with an oral dose of Momordica charantia. Besides, acute toxicity of the extract was also evaluated at concentration 2000 and 5000 mg/kg body weight. The extract was able to reduce blood glucose level in glucose and streptozotocin induced hyperglycaemic mice without causing hypoglycemic effect on fasting normoglycaemic mice. Moreover, mice appeared to be normal and no mortality was observed in the acute toxicity study after treated with up to 5000mg/kg of extract. These results indicated that the spray-dried Vernonia amygdalina water extract was a potential antidiabetic agent which does not induce hypoglycemic and acute toxicity on normal subject.